PENGARUH MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE (VCT) TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA SEKOLAH DASAR - Kusnia Afnani; Nurul Aini; Arie Widya Murni; Muhammad Assegaf Baalwi; Arif Nur Hidayat (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
This study was motivated by the need to implement a learning model that could improve students' learning outcomes in Pancasila Education, especially on the topic of Rules in the School Environment. The purpose of this study was to determine the effect of the Value Clarification Technique (VCT) learning model on the learning outcomes of third-grade students at SDN Sidokepung 1. This research employed a quantitative approach using a Pre-Experimental Design with a One-Shot Case Study design. The sample consisted of 19 third-grade students. Data were collected through a posttest to measure cognitive learning outcomes and observation sheets to assess affective and psychomotor learning outcomes. The data were analyzed using the Shapiro-Wilk normality test and the One-Sample t-Test. The results showed that all data were normally distributed. The hypothesis testing indicated significance values of 0.001 for the cognitive domain, 0.000 for the affective domain, and 0.000 for the psychomotor domain (Sig. < 0.05), indicating that the null hypothesis was rejected and the alternative hypothesis was accepted. The mean score of the cognitive domain was 84.20, which exceeded the minimum mastery criterion, while the affective and psychomotor domains obtained mean scores of 68.41 and 66.64, respectively, which were below the minimum mastery criterion. It can be concluded that the implementation of the Value Clarification Technique (VCT) learning model had a significant effect on the Pancasila Education learning outcomes of third-grade students at SDN Sidokepung 1. ABSTRAK                                                        Penelitian ini dilatarbelakangi oleh perlunya penerapan model pembelajaran yang dapat meningkatkan hasil belajar Pendidikan Pancasila pada materi Aturan di Lingkungan Sekolah. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran Value Clarification Technique (VCT) terhadap hasil belajar siswa kelas III SDN Sidokepung 1. Penelitian menggunakan pendekatan kuantitatif dengan jenis penelitian Pre-Experimental Design menggunakan desain One-Shot Case Study. Sampel penelitian berjumlah 19 siswa. Teknik pengumpulan data dilakukan melalui tes posttest pada ranah kognitif dan lembar observasi pada ranah afektif serta psikomotorik. Analisis data menggunakan uji normalitas Shapiro-Wilk dan uji hipotesis One-Sample t-Test. Hasil penelitian menunjukkan bahwa seluruh data berdistribusi normal. Hasil uji hipotesis menunjukkan nilai signifikansi pada ranah kognitif sebesar 0,001, ranah afektif sebesar 0,000, dan ranah psikomotorik sebesar 0,000 (Sig. < 0,05), sehingga H₀ ditolak dan Hₐ diterima. Rata-rata hasil belajar ranah kognitif sebesar 84,20 telah melebihi KKM, sedangkan ranah afektif sebesar 68,41 dan ranah psikomotorik sebesar 66,64 masih berada di bawah KKM. Dengan demikian, penerapan model pembelajaran Value Clarification Technique (VCT) berpengaruh terhadap hasil belajar Pendidikan Pancasila siswa kelas III SDN Sidokepung 1.